Web 2.0 applications in government web sites : prevalence, use and correlations with perceived web site quality - Chua, Alton Yeow Kuan (2013)
Purpose – The purpose of this paper is to investigate the extent to which Web 2.0 applications are prevalent in government web sites, the ways in which Web 2.0 applications have been used in government web sites, as well as whether the presence of Web 2.0 applications correlates with the perceived quality of government web sites.